Influence of water contamination on the sputtering of silicon with low-energy argon ions investigated by molecular dynamics simulations - Defoort-Levkov, Grégoire R. N.; Bahm, Alan; Philipp, Patrick (Beilstein Journal of Nanotechnology, 2022)
Focused ion beams (FIB) are a common tool in nanotechnology for surface analysis, sample preparation for electron microscopy and atom probe tomography, surface patterning, nanolithography, nanomachining, and nanoprinting. For many of these applications, a precise control of ion-beam-induced processes is essential. The effect of contaminations on these processes has not been thoroughly explored but can often be substantial, especially for ultralow impact energies in the sub-keV range. In this paper we investigate by molecular dynamics (MD) simulations how one of the most commonly found residual contaminations in vacuum chambers (i.e., water adsorbed on a silicon surface) influences sputtering by 100 eV argon ions. The incidence angle was changed from normal incidence to close to grazing incidence. For the simulation conditions used in this work, the adsorption of water favours the formation of defects in silicon by mixing hydrogen and oxygen atoms into the substrate. The sputtering yield of silicon is not significantly changed by the contamination, but the fraction of hydrogen and oxygen atoms that is sputtered largely depends on the incidence angle. This fraction is the largest for incidence angles between 70 and 80° defined with respect to the sample surface. Overall, it changes from 25% to 65%.
Keywords: angle dependency; argon ions; contamination; focused ion beams; ion bombardment; low energy; molecular dynamics; silicon; simulations; water

(untitled) - Wirtz, T.; De Castro, O.; Audinot, J.-N.; Philipp, P. (Annu. Rev. Anal. Chem., 2019)

(untitled) - Pillatsch, L.; Östlund, F.; Michler, J. (Prog. Cryst. Growth Charact. Mater., 2019)

(untitled) - Audinot, J.-N.; Philipp, P.; De Castro, O.; Biesemeier, A.; Hoang, Q. H.; Wirtz, T. (Rep. Prog. Phys., 2021)

(untitled) - Wirth, R. (Chem. Geol., 2009)

Thermoscientific 2018, 1–4

(untitled) - McPhail, D. S. (J. Mater. Sci., 2006)

(untitled) - Tseng, A. A. (Small, 2005)

(untitled) - Kawasegi, N.; Yamaguchi, M.; Kozu, T.; Morita, N.; Nishimura, K. (Precis. Eng., 2017)

2017 23rd International Conference on Automation and Computing (ICAC) - Hasan, R. M. M.; Luo, X. (Nanolithography: Status and challenges, 2017)

(untitled) - Sloyan, K.; Melkonyan, H.; Apostoleris, H.; Dahlem, M. S.; Chiesa, M.; Al Ghaferi, A. (Nanotechnology, 2021)

(untitled) - Llobet, J.; Krali, E.; Wang, C.; Arbiol, J.; Jones, M. E.; Pérez-Murano, F.; Durrani, Z. A. K. (Appl. Phys. Lett., 2015)

(untitled) - Córdoba, R.; Mailly, D.; Rezaev, R. O.; Smirnova, E. I.; Schmidt, O. G.; Fomin, V. M.; Zeitler, U.; Guillamón, I.; Suderow, H.; De Teresa, J. M. (Nano Lett., 2019)

(untitled) - De Teresa, J. M.; Orús, P.; Córdoba, R.; Philipp, P. (Micromachines, 2019)

(untitled) - Philipp, P.; Ngo, Q. K.; Shtein, M.; Kieffer, J.; Wirtz, T. (Anal. Chem. (Washington, DC, U. S.), 2013)

(untitled) - Prokhodtseva, A.; Mulders, J.; Vystavel, T. (Microsc. Microanal., 2017)

(untitled) - Lécz, Z.; Budai, J.; Andreev, A.; Ter-Avetisyan, S. (Phys. Plasmas, 2020)

(untitled) - Azuma, Y.; Kurokawa, A. (X-Ray Spectrom., 2019)

(untitled) - Barry, P. R.; Philipp, P.; Wirtz, T.; Kieffer, J. (J. Mass Spectrom., 2014)

(untitled) - Mach, J.; Šamořil, T.; Voborný, S.; Kolíbal, M.; Zlámal, J.; Spousta, J.; Dittrichová, L.; Šikola, T. (Rev. Sci. Instrum., 2011)

(untitled) - Rzeznik, L.; Fleming, Y.; Wirtz, T.; Philipp, P. (Beilstein J. Nanotechnol., 2016)

(untitled) - Yoshigoe, A.; Teraoka, Y. (Surf. Sci., 2003)

(untitled) - Pal, G.; Yadav, R. C.; Akhter, J.; Das, T.; Sarkar, A.; Mallik, C.; Bhandari, R. K. (J. Phys.: Conf. Ser., 2012)

(untitled) - Forrest, E.; Schulze, R.; Liu, C.; Dombrowski, D. (Int. J. Heat Mass Transfer, 2015)

(untitled) - Zhang, W.; van Duin, A. C. T. (J. Phys. Chem. B, 2017)

(untitled) - Yeon, J.; van Duin, A. C. T.; Kim, S. H. (Langmuir, 2016)

(untitled) - Fogarty, J. C.; Aktulga, H. M.; Grama, A. Y.; van Duin, A. C. T.; Pandit, S. A. (J. Chem. Phys., 2010)

(untitled) - Smith, R.; Harrison, D. E.; Garrison, B. J. (Phys. Rev. B, 1989)

(untitled) - Smith, R.; Beardmore, K.; Gras-Marti, A.; Kirchner, R.; Webb, R. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1995)

(untitled) - Stillinger, F. H.; Weber, T. A. (Phys. Rev. Lett., 1989)

(untitled) - Senftle, T. P.; Hong, S.; Islam, M. M.; Kylasa, S. B.; Zheng, Y.; Shin, Y. K.; Junkermeier, C.; Engel-Herbert, R.; Janik, M. J.; Aktulga, H. M.; Verstraelen, T.; Grama, A.; et al. (npj Comput. Mater., 2016)

(untitled) - Abolfath, R. M.; van Duin, A. C. T.; Brabec, T. (J. Phys. Chem. A, 2011)

(untitled) - Kowalik, M.; Hossain, M. J.; Lele, A.; Zhu, W.; Banerjee, R.; Granzier-Nakajima, T.; Terrones, M.; Hudson, E. W.; van Duin, A. C. T. (Catalysts, 2021)

(untitled) - Chenoweth, K.; van Duin, A. C. T.; Goddard, W. A. (J. Phys. Chem. A, 2008)

(untitled) - Newsome, D. A.; Sengupta, D.; Foroutan, H.; Russo, M. F.; van Duin, A. C. T. (J. Phys. Chem. C, 2012)

(untitled) - Soria, F. A.; Zhang, W.; Paredes-Olivera, P. A.; van Duin, A. C. T.; Patrito, E. M. (J. Phys. Chem. C, 2018)

(untitled) - Lechner, W.; Dellago, C. (J. Chem. Phys., 2008)

(untitled) - Martelli, F.; Ko, H.-Y.; Oğuz, E. C.; Car, R. (Phys. Rev. B, 2018)

(untitled) - van Duin, A. C. T.; Strachan, A.; Stewman, S.; Zhang, Q.; Xu, X.; Goddard, W. A. (J. Phys. Chem. A, 2003)

(untitled) - Costa Filho, R. N.; Alencar, G.; Skagerstam, B.-S.; Andrade, J. S., jr (EPL, 2013)

(untitled) - Kresse, G.; Hafner, J. (Phys. Rev. B, 1993)

(untitled) - Kresse, G.; Hafner, J. (Phys. Rev. B, 1994)

(untitled) - Kresse, G.; Furthmüller, J. (Comput. Mater. Sci., 1996)

(untitled) - Kresse, G.; Furthmüller, J. (Phys. Rev. B: Condens. Matter Mater. Phys., 1996)

(untitled) - Perdew, J. P.; Burke, K.; Ernzerhof, M. (Phys. Rev. Lett., 1996)

(untitled) - Blöchl, P. E. (Phys. Rev. B, 1994)

(untitled) - Kresse, G.; Joubert, D. (Phys. Rev. B: Condens. Matter Mater. Phys., 1999)

(untitled) - Tkatchenko, A.; Scheffler, M. (Phys. Rev. Lett., 2009)

pair _ style hybrid command, LAMMPS documentation

(untitled) - Rappe, A. K.; Goddard, W. A., III (J. Phys. Chem., 1991)

(untitled) - Nakano, A. (Comput. Phys. Commun., 1997)

(untitled) - Aktulga, H. M.; Fogarty, J. C.; Pandit, S. A.; Grama, A. Y. (Parallel Comput., 2012)

(untitled) - Plimpton, S. (J. Comput. Phys., 1995)

(untitled) - Grønbech-Jensen, N.; Farago, O. (Mol. Phys., 2013)

(untitled) - Kamiyama, E.; Sueoka, K. (J. Electrochem. Soc., 2010)

(untitled) - Chen, J.; Zhang, G.; Li, B. (J. Phys. Soc. Jpn., 2010)

(untitled) - Simonton, R. B.; Kamenitsa, D. E.; Ray, A. M.; Park, C.; Klein, K. M.; Tasch, A. F. (Nucl. Instrum. Methods Phys. Res., Sect. B, 1991)

(untitled) - Stegmann, H.; Ritz, Y.; Utess, D.; Hübner, R.; Zschech, E. (AIP Conf. Proc., 2009)

(untitled) - Ren, Y.; Lei, D.; Yao, F.; Wang, Z. (AIP Conf. Proc., 2019)

(untitled) - Abdel-Samad, S.; Abdel-Bary, M.; Kilian, K. (Vacuum, 2005)

Secondary Ion Mass Spectrometry - van der Heide, P. (John Wiley & Sons, 2014)

(untitled) - Demaison, J.; Herman, M.; Lievin, J. (Int. Rev. Phys. Chem., 2007)

(untitled) - Tuttle, B.; Van de Walle, C. G. (Phys. Rev. B: Condens. Matter Mater. Phys., 1999)

(untitled) - Baur, W. H. (Acta Crystallogr., Sect. B: Struct. Crystallogr. Cryst. Chem., 1977)

(untitled) - Niu, C.-Y.; Wang, J.-T. (J. Chem. Phys., 2013)

(untitled) - Kopera, B. A. F.; Retsch, M. (Anal. Chem. (Washington, DC, U. S.), 2018)

(untitled) - Samela, J.; Nordlund, K.; Keinonen, J.; Popok, V. N. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2007)

(untitled) - Allen, L. P.; Insepov, Z.; Fenner, D. B.; Santeufemio, C.; Brooks, W.; Jones, K. S.; Yamada, I. (J. Appl. Phys., 2002)

(untitled) - Samela, J.; Nordlund, K.; Keinonen, J.; Popok, V. N.; Campbell, E. E. B. (Eur. Phys. J. D, 2007)

(untitled) - Zalm, P. C. (J. Appl. Phys., 1983)